Acurácia e precisão: Revendo os conceitos de forma acurada - Monico, João Francisco Galera [UNESP]; dal Póz, Aluir Porfírio [UNESP]; Galo, Maurício [UNESP]; dos Santos, Marcelo Carvalho; de Oliveira, Leonardo Castro (My University, 2009)
Accuracy concepts that involve systematic and random effects and precision, that involves only random ones, are reviewed in this paper. An objective discussion is presented based on the definitions that appear in the literature, followed by examples that may be enough to clarify some concepts and allow the extension for other applications. The discussion presented aims at raising eventual inconsistencies in the interpretations so as to provide better possibilities of use for those involved with this topic, which is fundamentally important in the quality analysis of cartographic, geodetic and remote sensing or photogrammetric products.
Accuracy and Precision: Reviewing the concepts by means of an accurate procedure
Keywords: Accuracy; Bias; Precision; Systematic and Random Effects